Lifetime estimation for optocouplers using accelerated degradation test - Kang, Minkoo; Lee, Sunjae; Park, Heedo; Jang, Joongsoon; Park, Sangchul; Kim, Jong Ho; Yoo, Chan Sei (Quality and Reliability Engineering International, 2022)
Instrumentation and control systems significantly affect the safety and reliability of nuclear power plants. In this study, we analyze the cause of failure of the electronic card constituting the instrumentation and control system as it is the most typical reason for the failure of optocouplers. The lifetime of optocouplers must be predicted accurately to ensure high-reliability nuclear power plants. While acceleration tests have been performed to predict the lifetime of optocouplers more efficiently, it is preferable to perform accelerated degradation tests rather than accelerated life tests. In this paper, accelerated degradation tests are performed on optocouplers at various temperatures and voltages. To derive the degradation curve model of the optocoupler using the results of accelerated degradation tests, we use the most suitable model from OriginLab. The parameter values of the proposed degradation curve model are calculated by applying the Arrhenius model and Weibull distribution, and the lifetime of the optocoupler is estimated by using the proposed degradation curve model.
Keywords: Accelerated degradation tests; Accelerated life tests; Acceleration tests; Case-studies; Curve modeling; Electronic cards; High reliability; Instrumentation and control system; Lifetime estimation; Optocouplers